Green Reduction of Graphene Oxide (GO) from Coconut Shell Using Rose Water in Various Temperature: Biaunik Niski Kumila, Nihlah Zaidah, Hamdan Hadi Kusuma - Biaunik Niski Kumila Biaunik Niski Kumila; Nihlah Zaidah Nihlah Zaidah; Hamdan Hadi Kusuma Hamdan Hadi Kusuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
Graphene and its related materials have attracted much interest in various applications regarding its exceptional physical, chemical, and mechanical properties. Reduction of graphene oxide (GO) from natural resources is recognized as one of the promising methods for low-cost and large-scale production of graphene-based materials. However, the reduction of GO is generally involves the application of toxic and poisonous substances. To counter this challenge, the green reduction which employ non-hazardous substances was introduced by numerous researchers. In this research, the green reduction of graphene oxide from coconut shell was investigated using rose water at room temperature, 70, 80, 90, and 1000 C. The prepared GO and green reduced GO (rGO) were characterized by X-Ray diffraction (XRD), Scanning Electron Microscope - Energy Dispersive X-Ray (SEM-EDX), Fourier transform infrared (FTIR), and I-V measurement. The low-cost and easy-handle green reduction of GO was obtained by immersing in rose water at room temperature which exhibit carbon to oxygen ratio, C/O of 2.97. Moreover, the effect of oxygenated-functional group to the electrical properties was also strongly discussed.